Cardiac and Vascular Target Organ Damage in Pediatric Hypertension - Khoury, Michael; Urbina, Elaine M. (Frontiers in Pediatrics, 2018)
Atherosclerosis begins in youth and is associated with the presence of numerous modifiable cardiovascular risk factors, including hypertension. Pediatric hypertension has increased in prevalence since the 1980’s but has plateaued in recent years. Elevated blood pressure levels are associated with impairments to cardiac and vascular structure and both systolic and diastolic function. Blood pressure-related increases in left ventricular mass and abnormalities in cardiac function are associated with hard cardiovascular events in adulthood. In addition to cardiac changes, key vascular changes occur in hypertensive youth and adults. These include thickening of the arteries, increased arterial stiffness, and decreased endothelial function. This review summarizes the epidemiologic burden of pediatric hypertension, its associations with target organ damage of the cardiac and vascular systems, and the impact of these adverse cardiovascular changes on morbidity and mortality in adulthood.